The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0262053
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic left ventricular stroke work index: An integrated noninvasive measure of shock severity

Abstract: Background Echocardiographic findings vary with shock severity, as defined by the Society for Cardiovascular Angiography and Intervention (SCAI) shock stage. Left ventricular stroke work index (LVSWI) measured by transthoracic echocardiography (TTE) can predict mortality in the cardiac intensive care unit (CICU). We sought to determine whether LVSWI could refine mortality risk stratification by the SCAI shock classification in the CICU. Methods We included consecutive CICU patients from 2007 to 2015 with TTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The LVSW and CPO are parameters of overall LV function, but the LVSWM and CPOM represent the performance of unit myocardium or myocardial workload. Previous studies on the LVSW index, CPO index, or peak CPOM quantified with stress echocardiography has displayed important prognostic values of these parameters in cardiovascular disease [35][36][37][38][39][40][41][42]. Thus, it is hoped that this work will stimulate further research on these important measures of LV myocardial performance to improve the accuracy of cardiac function assessment and therefore to optimize clinical decisions in cardiovascular disease.…”
Section: Perspectivesmentioning
confidence: 82%
“…The LVSW and CPO are parameters of overall LV function, but the LVSWM and CPOM represent the performance of unit myocardium or myocardial workload. Previous studies on the LVSW index, CPO index, or peak CPOM quantified with stress echocardiography has displayed important prognostic values of these parameters in cardiovascular disease [35][36][37][38][39][40][41][42]. Thus, it is hoped that this work will stimulate further research on these important measures of LV myocardial performance to improve the accuracy of cardiac function assessment and therefore to optimize clinical decisions in cardiovascular disease.…”
Section: Perspectivesmentioning
confidence: 82%
“…Similar observations were made in patients with major adverse cardiovascular events (Tona et al, 2021). Also, it has been shown that decreased LV stroke work index is associated with diminished LV systolic and diastolic function in cardiac intensive care unit patients (Jentzer et al, 2022). Also, we found that stroke work is significantly lower in the in the TRAF2 mice perhaps indicating a diminished cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, invasive data from arterial pulsatility and temporary mechanical circulatory support platforms can add to the understanding of the clinical scenario. There is a paucity of data regarding the combination of invasive and noninvasive parameters, timing of evaluation, and adequate correlation with clinical and echocardiographic findings for CS and these questions merit further study [25 ▪▪ ].…”
Section: Cardiogenic Shock Detection and Classificationmentioning
confidence: 99%